DESIGN AND IMPLEMENTATION OF ROAD FOLLOWING ON A SELF-DRIVING CAR PROTOTYPE BASED ON JETSON NANO WITH 5G* NETWORK - Maitsa Gunawan, Syaghina
The development of self-driving car technology offers great potential in enhancing transportation efficiency and safety. Self-driving cars can reduce human involvement in driving, potentially lowering traffic accident rates often caused by human error. This technology is also expected to optimize travel and reduce